User Interface concept for AI-supported clinical decision making in prehospital emergency care - Andersson, Jens; Maxstad, Elin (My University, 2022)
This thesis investigated how new technology could be implemented in the prehospital healthcare with the aim of introducing a digital AI-powered clinical decision support. Through interviews, on-site observation and a focus group of ambulance nurses an idea of the situation was established. With that as a baseline, the development of three different deliverables started; firstly, a digital interface meant for data collection feeding into the machine learning of the AI. Secondly, a representation of how a clinical decision support should be presented and thirdly, a rough interface proposal of how a collection of several existing digital tools could be integrated to one seamless solution, acting as a digital toolbox. All three concepts were well received amongst the few involved ambulance nurses. A hypothesis for the reason of such positive reception is a combination of multiple things. A few of those being actual good design work, the current situation of poor tools being the only comparison and that some deliverables were very conceptual with fidelity gaps being filled in with hopes and expectations of the perfect tool.